PENERIMAAN IBU SEBAGAI KUNCI PENTING INTERAKSI IBU-ANAK PADA ANAK BERKEBUTUHAN KHUSUS - Rahayu, Witri Evilia; Ramadhanty, Rizki Dwi; Alfiasari (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2022)
Mother-child interaction for children with special needs is one of the keys to a positive parenting process . This study aimed to analyze the influence of social support and mother's acceptance on mother-child interaction in families with children with special needs. This research used a quantitative approach and an explanatory study design. The research location is the Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) area, with the study population were mothers with ABK aged 4-20 years. The sampling technique used non-probability sampling through convenience sampling. The total number of mothers as respondents in the study were 80 mothers. The results showed that the mother's social support was in the moderate category with an average index value of 64.61; maternal acceptance was in the high category with an average index value of 83.25; and the mother-child interaction was in the moderate category with an index average value of 71.3. The results of the correlation test showed that social support was significantly positively related to maternal acceptance and mother-child interaction. In addition, maternal acceptance has a significant positive relationship with mother-child interaction. The regression model shows that the mother-child interaction is significantly positively influenced by maternal acceptance.